Unavailable - de Lima, Pedro E. (Boletim do Museu Nacional: Nova Série: Antropologia, 2022)
The present paper reffers to the determination of blood groups O, A, B and AB among the Indian inhabitants of the Upper Xingu River, state of Mato Grosso, representatives of the tribes: Kamaiurá, Waurá, Mehinako, Kalapalo and Bakairí. A total of 377 observations were made, of which only one was classified as group A, the rest being entirely on the group O. The only individual representative of the group A was a Bakairí woman, half-breed of brazilian and Indian. The result, dominance of group O, confirms other similar observations made on Brazilian Indians.